Die Ethnoethik Bernard Bolzanos - Grzywacz, Małgorzata (Studia Germanica Posnaniensia, 2018)
Bernard Bolzano (1781-1848) is well-known to large circles as a logician and mathematician. In the above article the main point of interest became its social ethics whose practical application was perceived by Bolzano in quieting conflicts and feuds which then troubled the Habsburg monarchy. The ethics of Bolzano is in opposition to the moral law of Kant, rejects his subjectivity. In practice it means submission of man and his behaviour to verification by the moral law to which in tum even God is submitted. Surrender was the only way of solving conflicts of Czechs and Germans Irving together in Germany to which "Speeches for elevation" (Erbauungsreden) were devoted and which were delivered to the students in Prague. It woke up the dormant intellectual elites, however, it did not overcome the supremacy of romantic ideas of Friedrich Schlegel which triumphed in the Austrian monarchy of the middle of the 19th century.